PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMKN 1 BOJONEGORO - Rachmania Arsyani; Imami Arum Tri Rahayu (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the influence of entrepreneurial knowledge on entrepreneurial interest among 11th and 12th-grade students majoring in Fashion Design Production (DPB) at SMKN 1 Bojonegoro. The high unemployment rate among vocational high school (SMK) graduates and the low percentage of Fashion Design graduates who pursue entrepreneurship underscore the urgency of this research. This study employs a quantitative ex post facto approach. The research subjects comprised the entire population of 11th and 12th-grade DPB students at SMKN 1 Bojonegoro for the 2025/2026 academic year, totaling 58 students. Data on entrepreneurial knowledge were collected through documentation of learning achievement scores in the Creative Project and Entrepreneurship (PKK) course, while data on entrepreneurial interest were obtained through the distribution of closed-ended questionnaires using a Likert scale. Data analysis was conducted using simple linear regression with the aid of statistical software. The results showed that students' entrepreneurial knowledge was in the very good category (mean 91.85), and entrepreneurial interest was generally in the high category (mean 65.19). However, hypothesis testing proved that there was no significant influence of entrepreneurial knowledge on entrepreneurial interest among DPB students at SMKN 1 Bojonegoro, as indicated by a significance value of 0.182 > 0.05 and a very weak contribution of 3.2%. The conclusion of this study is that high academic understanding of entrepreneurship does not directly translate into a desire for real action, because understanding the complexities of business actually makes students more cautious, while the drive to become an entrepreneur is more dominated by external factors beyond cognitive education in the classroom.